PPM PENGUSAHA KECIL T-SHIRT CRAWL AND JACK DALAM PENGEMBANGAN UMKM - Nur Holifah; Novita Maulida Ikmal; Indriastuti (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2025)
Crawl and Jack is a plain t-shirt business that is currently in great demand by the younger generation. However, in a newly established business like this, there are many obstacles faced, such as increasing consumer demand for the availability of goods, design innovation. So that it makes business owners a little overwhelmed with the demand. Various custom clothing designs can attract consumers who are indeed fond of using the t-shirt collection. The availability of this custom design greatly influences the increasing sales of Crawl and Jack T-Shirt products. The Crawl and Jack T-Shirt business is managed by Mrs. Binti Nurhayati. We see the importance of raising the UMKM product of this crawl and jack t-shirt entrepreneur because we see her persistence in starting a business during a pandemic so that the product is able to survive and grow wider until now. The problems experienced are limited capital for the availability of singer sewing machines, not yet proficient in making various custom designs according to customer requests. In addition, as an innovation, this business needs to optimize management and marketing of promotional facilities so that the business can survive in the future. The solutions we offer for business development are First, Buying production support equipment units, in this case a singer sewing machine. Second, holding design training and direct online marketing practice.